2015
DOI: 10.1371/journal.pone.0129595
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Functional Connectivity of Default Mode and Set-Maintenance Networks in Ornithine Transcarbamylase Deficiency

Abstract: Background and PurposeOrnithine transcarbamylase deficiency (OTCD) is an X-chromosome linked urea cycle disorder (UCD) that causes hyperammonemic episodes leading to white matter injury and impairments in executive functioning, working memory, and motor planning. This study aims to investigate differences in functional connectivity of two resting-state networks—default mode and set-maintenance—between OTCD patients and healthy controls.MethodsSixteen patients with partial OTCD and twenty-two control participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…In agreement with these reports, our group has identified that patients with distal UCD (where ammonia levels are not as elevated as in proximal disorders) have a high frequency of epilepsy and cognitive dysfunction, raising the possibility that seizures may be associated with other biochemical abnormalities in distal UCD [36,71]. Additionally, we have shown that disrupted neural networks underlying working memory are a consistent finding in UCD patients with mild as well as severe symptoms [25,46]. These studies strengthen the importance of understanding the incidence/prevalence of epilepsy in patients with UCDs and if and how this may affect later cognitive function.…”
Section: Seizures In Ucdsupporting
confidence: 84%
See 1 more Smart Citation
“…In agreement with these reports, our group has identified that patients with distal UCD (where ammonia levels are not as elevated as in proximal disorders) have a high frequency of epilepsy and cognitive dysfunction, raising the possibility that seizures may be associated with other biochemical abnormalities in distal UCD [36,71]. Additionally, we have shown that disrupted neural networks underlying working memory are a consistent finding in UCD patients with mild as well as severe symptoms [25,46]. These studies strengthen the importance of understanding the incidence/prevalence of epilepsy in patients with UCDs and if and how this may affect later cognitive function.…”
Section: Seizures In Ucdsupporting
confidence: 84%
“…The neuroimaging/neurocognitive studies we performed as part of the UCDC focused on adolescents and adults with OTCD. Our collective studies demonstrated that OTCD heterozygous females have changes in function of the prefrontal cortex (PFC) in association with an altered neurocognitive profile in working memory, executive functioning, and attention [46]. fMRI can allow us to understand how the brain constructs neural networks to perform cognitive tasks, probe how these networks are altered in brain disorders, and allow us to follow recovery.…”
Section: How Can Neuroimaging Help Us Probe Markers Of Neurological Dmentioning
confidence: 99%
“…Internodal functional connectivity in the default mode network (DMN) and set-maintenance network (SMN) is reduced in patients with partial OTCD compared to controls, most likely due to HA-related white matter damage (Pacheco-Colón , et al, 2015). Because several of the affected areas are involved in executive functioning, it is postulated that this reduced connectivity may be an underlying cause of the deficits OTCD patients display in this cognitive domain.…”
Section: What Are the Neuroimaging Abnormalities In Ucd And How Can Nmentioning
confidence: 99%
“…Additionally, the brains of individuals with OTCD show alterations in functional connectivity at rest. Internodal functional connectivity in the default mode network (DMN) and set-maintenance network (SMN) is reduced in patients with partial OTCD compared to controls, most likely due to HArelated white matter damage (Pacheco-Colón et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Episodes of HA cause injury to the brain's white matter. We and others have shown that even "asymptomatic" OTCD is associated with an altered neurocognitive profile in an array of cognitive subdomains based in the prefrontal cortex (PFC), such as working memory, executive cognition and attention [7][8][9]. These deficits contribute significantly to disability.…”
Section: Introductionmentioning
confidence: 99%